Settlement of Linear Band Pottery culture in the area of the Kuyavian Lakeland in the light of field-walking survey realized within the framework of the program “Archaeological sources in the region of the Wietrzychowice Culture Park” - Papiernik, Piotr; Płaza, Dominik Kacper; Wicha, Joanna (Acta Archaeologica Lodziensia, 2018)
Archaeological excavations in the region of today’s Wietrzychowice Culture Park were begun in the 1930s by professor Konrad Jażdżewski himself and were carried on under his supervision in the 1950s. Field works were resumed by the Museum of Archaeology and Ethnography in Łódź and the Konrad Jażdżewski Foundation of Archaeological Research in 2009. They aim at conducting interdisciplinary research, which would provide a complete picture of the settlement of the Funnel Beaker culture in the vicinity of megalithic cemeteries at Wietrzychowice and Gaj. A very important element of the programme is non-invasive work done as the project “Archaeological Sources in the region of Wietrzychowice Culture Park“, completed as part of the programme of the Minister of Culture and Cultural Heritage, called “Cultural Heritage”, priority 5, “Protection of Archaeological Artefacts”. Field works have yielded artefacts dating back to the period between the late Palaeolithic and the Middle Ages. One of the most important results of the field surveys has been the discovery of a new group of sites of the Linear Pottery culture. Artefacts of that type were unearthed on 44 sites. It is an unexpected result, as the programme of Archaeological Picture of Poland carried out in the 1980s revealed only two such sites on the territory in question, situated 20km away from a well-recognised settlement cluster of the Linear Pottery culture in the region of Brześć Kujawski. The analysis of the pottery unearthed on separate sites clearly indicates the cultural provenience of particular assemblages. In the case of table ware (delicate work) these are fragments of thin-walled, or more rarely mediumwalled forms, made of processed clay (without silt), almost completely void of thinning admixture. In the case of kitchen ware (coarse work) , we can observe vegetation admixture with sand and grog (chamotte) admixture. Delicate vessel pottery is mainly decorated with engraved lines in various patterns, frequently accompanied by note motifs. Decoration on kitchen ware is limited to finger and fingernail imprints and knobs placed in different parts of the vessels.